PEWARISAN NILAI-NILAI BUDAYA RUMAH LONTIOK KEPADA GENERASI MUDA - Isjoni, Isjoni; Fikri, Asyrul; Riantama, M. Yogi; Yuliantoro, Yuliantoro (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to look at the process of inheriting the cultural values of lontiok houses to the younger generation of Kampar people specifically around the lontiok house environment. The research method is descriptive qualitative. Data collection techniques using observation and interviews. The analysis is data reduction, data presentation and conclusion drawing. The results of the study, namely, between traditional houses and cultural values can not be separated from the role of humans as cultural beings who inherit the culture. Inheritance of cultural values is done in two ways, namely through the tradition of hereditary from the ninik mamak to the younger generation and through tourism awareness groups (Pok derwis). education in schools is very important. This is done to preserve the culture so that it does not disappear in the midst of an increasingly developed and developing era.